1987
DOI: 10.1507/endocrj1954.34.13
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Clinical Assessment of a Radioreceptor Assay for Thyrotropin-Binding Inhibitor Immunoglobulins

Abstract: We tried to improve the sensitivity of a radioreceptor assay for thyrotropinbinding inhibitor immunoglobulins (TBII) by modifying assay conditions. About a twofold increase in sensitivity without a loss of reproducibility was obtained by prolonging the incubation of the receptors with test serum from15to120 min before the addition of125I-labeled thyrotropin. In20untreated, 49treated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

1987
1987
2003
2003

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 18 publications
0
7
1
Order By: Relevance
“…Although the buffer of 10 mmol/1 TRIS-HC1, 50 mmol/1 NaCl was rec¬ ommended in TBII assay using thyroid mem¬ branes (5)(6)(7)12,14), our observation in the present study revealed that modified Hanks'(-) was the best of the four buffers tested and TBII activities were much higher in the modified hypotonie Hanks'(-) medium using cells. [I2:T]bTSH binding to FRTL-5 cells was much greater in the absence than in the presence of NaCl, in agreement with the observa¬ tion by others (10,17,18).…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Although the buffer of 10 mmol/1 TRIS-HC1, 50 mmol/1 NaCl was rec¬ ommended in TBII assay using thyroid mem¬ branes (5)(6)(7)12,14), our observation in the present study revealed that modified Hanks'(-) was the best of the four buffers tested and TBII activities were much higher in the modified hypotonie Hanks'(-) medium using cells. [I2:T]bTSH binding to FRTL-5 cells was much greater in the absence than in the presence of NaCl, in agreement with the observa¬ tion by others (10,17,18).…”
Section: Discussioncontrasting
confidence: 51%
“…TBII assay A radioreceptor TBII assay using detergent solubilized porcine thyroid membranes (TBII-pm) was carried out using a commercial kit developed by Southgate et al (7) with a minor modification (14). Results were expressed as follows: (1-specific [12TjTSH binding in the presence of a test sample/specific [12T]TSH binding in the presence of a pooled normal sample) x 100%.…”
Section: Preparation Of Serum Crude Immunoglobulin Fractionmentioning
confidence: 99%
“…An impaired response of the thyroid to TSAb in ophthalmic Graves' disease, presumably owing to some de¬ structive change, has been postulated (Teng et al 1977) and is partly proven by the fact that some of the patients are hypothyroid (Christy et al 1977). As another possibility, some qualitative difference between the TSH receptor antibodies in ophthal¬ mic and thyrotoxic Graves' disease might be spe¬ culated, considering the reported lower incidence of TSH-binding inhibitor immunoglobulins in pa¬ tients with ophthalmic than in those with thyro¬ toxic Graves' disease (Teng et al 1977;Konishi et al 1987). However, the in vivo mechanism by which TSAb induce clinical manifestation of hyperthyroidism still remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…The first one, which has been widely used in clinical practice for two decades, is a precipitation assay with solubilized porcine thyroid TSH-receptor [13,14]; the second is an improved system that uses test tubes coated with recombinant human TSH receptor [15]. TBII was expressed as % binding inhibition to facilitate comparison of the two systems.…”
Section: Methodsmentioning
confidence: 99%